Delineation of Vulnerable Areas Affected by the Eruption of Mount Agung, Bali - Erfani, Sandri; Naimullah, Muhammad; Gracia, Christas; Uzzahra, Sheilla Annisa (JURNAL GEOGRAFI, 2024)
Vulnerability is a condition of a community or society that causes the inability to face the threat of disaster. Geographic information systems (GIS) have become essential tools in evaluating natural hazards and risks which is an aspect to define vulnerability of the volcano eruption-affected area. Based on activity of volcano, it is necessary to delineate the vulnerability of areas affected by the eruption of Mount Agung by integrating the Mount Agung Area Network Map and Geological Map with physical vulnerability data and social vulnerability. This research using processing methods and spatial analysis of Geographic Information Systems (GIS) and remote sensing methods. Geographic Information System (GIS) is used to create vulnerability maps using scoring, weighting, and overlay methods. The data used for making the vulnerability map include administrative boundaries, DEM (Digital Elevation Model), secondary data from the BPS 2020 Karangasem Regencyt in Figures, geological maps, settlement data and land cover maps. The results based on these data show the number of areas affected by the eruption of Mount Agung, the data states that the data area with low vulnerability has an area of 0.001490 Ha. Medium vulnerability data has an eruption affected area of 47.024493897 Ha. While the high vulnerability has an affected area of 36.878843877 Ha. Differences in the level of vulnerability are influenced by social vulnerability, physical vulnerability, and environmental vulnerability.Keywords: Delineation, Eruption, GIS, Mount Agung, Vulnerability